Schlemm’s Canal Endothelium Cellular Connectivity in Giant Vacuole and Pore Formation in Different Flow-type Areas: A Serial Block-Face Scanning Electron Microscopy Study - Swain, David L.; Yasmin, Senila; Fernandes, Beatriz; Lamaj, Ganimete; Su, Yanfeng; Gong, Haiyan (Frontiers in Cell and Developmental Biology, 2022)
Glaucoma is associated with increased resistance in the conventional aqueous humor (AH) outflow pathway of the eye. The majority of resistance is thought to reside in the juxtacanalicular connective tissue (JCT) region of the trabecular meshwork and is modulated by the inner wall (IW) endothelial cells of Schlemm’s canal (SC). The IW cells form connections with the underlying JCT cells/matrix, and these connections are thought to modulate outflow resistance. Two ways by which AH crosses the IW endothelium are through: 1) the formation of outpouchings in IW cells called giant vacuoles (GVs) and their intracellular pores (I-pores), and 2) intercellular pores between two adjacent IW cells (B-pores). AH outflow is segmental with areas of high-, low-, and non-flow around the circumference of the eye. To investigate whether changes in cellular connectivity play a role in segmental outflow regulation, we used global imaging, serial block-face scanning electron microscopy (SBF-SEM), and 3D reconstruction to examine individual IW cells from different flow areas of ex vivo perfused normal human donor eyes. Specifically, we investigated the differences in cellular dimensions, connections with JCT cells/matrix, GVs, and pores in SC IW cells between high-, low-, and non-flow areas. Our data showed that: 1) IW cell-JCT cell/matrix connectivity was significantly decreased in the cells in high-flow areas compared to those in low- and non-flow areas; 2) GVs in the cells of high-flow areas had significantly fewer connections beneath them compared to GVs in the cells of low- and non-flow areas; 3) Type IV GVs (with I-pores and basal openings) had significantly fewer connections beneath them compared to Type I GVs (no I-pore or basal opening). Our results suggest that a decreased number of cellular connections between the IW and JCT in high-flow areas is associated with increased numbers of GVs with I-pores and larger Type IV GVs observed in previous studies. Therefore, modulating the number of cellular connections may affect the amount of high-flow area around the eye and thereby modulate AH outflow.